2021
DOI: 10.1038/s41524-021-00521-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of high thermoelectric performance in the low-dimensional metal halide Cs3Cu2I5

Abstract: Metal halides have emerged as a new generation of semiconductors with applications ranging from solar cells to chemical sensors. We assess the thermoelectric potential of Cs3Cu2I5, which has a crystal structure formed of zero-dimensional [Cu2I5]3− anionic clusters that are separated by Cs+ counter cations. We find the compound exhibits the characteristics of a phonon-glass electron-crystal with a large imbalance in the conduction of heat and electrons predicted from first-principles transport theory. Strong an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 66 publications
(63 reference statements)
3
35
1
Order By: Relevance
“…The real part (ε 1 ) at photon energy → 0 eV is the optical dielectric constant (ε ∞ ). We obtained ε ∞ = 3.2 from the Wannier interpolation with HSE06, which is slightly lower than ε ∞ = 3.8 calculated from density-functional perturbation theory (DFPT) using the PBEsol exchange-correlation functional . This originates from the band gap underestimation by DFT/PBEsol as the optical dielectric constant is inversely proportional to the band gap .…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The real part (ε 1 ) at photon energy → 0 eV is the optical dielectric constant (ε ∞ ). We obtained ε ∞ = 3.2 from the Wannier interpolation with HSE06, which is slightly lower than ε ∞ = 3.8 calculated from density-functional perturbation theory (DFPT) using the PBEsol exchange-correlation functional . This originates from the band gap underestimation by DFT/PBEsol as the optical dielectric constant is inversely proportional to the band gap .…”
mentioning
confidence: 69%
“…Pristine Crystal . Because we have recently provided analysis of crystal structure and electronic band structure of Cs 3 Cu 2 I 5 , here we briefly summarize them. In Figure a, the primitive unit cell (space group Pnma ) of Cs 3 Cu 2 I 5 that contains 40 atoms is shown.…”
mentioning
confidence: 99%
“…22,37,55–61 More recently, metal halides of Cu with compositions of Cs 3 Cu 2 I 5 , Cs 3 Cu 2 Br 5 and Rb 2 CuX 3 (X = Cl, Br) have also been synthesised. 35,62 Among the metallic Cu 2D NCs seeded growth materialised NCs with PdCu and PdPtCu compositions. 63 Apart from these, many other unconventional compositions such as Cu 3 P 1− x S x and CsCu 5 S 3 have also been achieved using colloidal methods.…”
Section: Colloidal 2d Copper Based Ncsmentioning
confidence: 99%
“…Moreover, they are also predicted as phonon glass electron crystals with a thermoelectric figure of merit ∼ 2.6. 35 In addition, the high ionic mobility of Cu + in a Cu-based NC lattice benefits foreign cation substitution forming multinary NCs, which is not feasible for most other 2D NCs. 36,37 These Cu-based NCs can possess both layered and non-layered structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have predicted zT as high as 2.6 in low dimensional metal halide perovskite derivatives. 17 Many experimental studies have reported metal halide perovskites with high Seebeck coefficient, 18,19 and ultralow thermal conductivity, [20][21][22][23][24][25] and have also reported doping methods to tune their electrical conductivity. 20,22,26 However, doping of halide perovskite materials remains challenging, which may be due to ionic compensation of charged point defects 27 and a defect tolerant electronic structure deriving from bonding orbitals at the conduction band minimum (CBM) as well as antibonding orbitals at the valence band maximum (VBM).…”
Section: Introductionmentioning
confidence: 99%